2014
DOI: 10.3390/s140713243
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Soil Profiling Using a Galvanic Contact Resistivity Scanning Approach

Abstract: Proximal sensing of soil electromagnetic properties is widely used to map spatial land heterogeneity. The mapping instruments use galvanic contact, capacitive coupling or electromagnetic induction. Regardless of the type of instrument, the geometrical configuration between signal transmitting and receiving elements typically defines the shape of the depth response function. To assess vertical soil profiles, many modern instruments use multiple transmitter-receiver pairs. Alternatively, vertical electrical soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Khan et al [43] reported a low EC a , between 2.1 and 35.5 mS m −1 , on an orthic Humo-ferric podzol while Pan et al [59] indicated a low EC a between 1.36 and 3.29 mS m −1 in a sandy soil. Martini et al [60] also observed a low EC a , between 0 and 24 mS m −1 , with a very small range of spatial variation which was predominantly attributed to the low heterogeneity of soil texture (Sand = 6%-28%, Silt = 55%-79%, Clay = 13%-25%).…”
Section: Discussionmentioning
confidence: 98%
“…Khan et al [43] reported a low EC a , between 2.1 and 35.5 mS m −1 , on an orthic Humo-ferric podzol while Pan et al [59] indicated a low EC a between 1.36 and 3.29 mS m −1 in a sandy soil. Martini et al [60] also observed a low EC a , between 0 and 24 mS m −1 , with a very small range of spatial variation which was predominantly attributed to the low heterogeneity of soil texture (Sand = 6%-28%, Silt = 55%-79%, Clay = 13%-25%).…”
Section: Discussionmentioning
confidence: 98%
“…Besides, the newest Veris models (V2000XA, V3100, V3150) present two pairs of potential measurement electrodes instead of just one, which jointly enable a simple soil profiling of EC a with two depths. The coulter electrodes are also sold individually and therefore users can build their own craft ER sensor systems [47].…”
Section: Commercial Sensors For Measuring Ec 71 Electrical Resistivmentioning
confidence: 99%
“…EC a measurements have been widely used to characterize soil salinity at field scale. Modern mobile ER measurement systems based on a four-point array along with the use of GPS allow to elaborate 3D maps of EC a in agricultural fields, giving rise to ER Imaging (ERI) in soil studies and agriculture [47,62]. Good contact between the electrodes and the soil is maybe the most important constraint to have reliable EC a measurements using ER.…”
Section: Soil Salinity Mappingmentioning
confidence: 99%
“…Moreover, real-time soil resistivity measurement is important to map spatial farmland heterogeneity for precision farming applications. A useful approach for soil-property investigations is to use proximal soil measurements that combine soil sensors and data analysis methods to obtain high resolution soil data of the huge farmland [18]. Two portable systems are used to measure real time soil resistivity or conductivity of soil in agricultural studies-electrode-soil contact based system and noncontact electromagnetic induction (EM) system.…”
Section: Introductionmentioning
confidence: 99%